Use of coaching and technology to improve blood pressure control in Black women with hypertension: Pilot randomized controlled trial study. Issue 1 (20th December 2022) - Abel, Willie M.; Efird, Jimmy T.; Crane, Patricia B.; Ferdinand, Keith C.; Foy, Capri G.; DeHaven, Mark J.
Abstract: Hypertension is the main cause of cardiovascular disease, especially in women. Black women (58%) are affected by higher rates of hypertension than other racial/ethnic groups contributing to increased cardio‐metabolic disorders. To decrease blood pressure (BP) in this population, a pilot randomized controlled trial was conducted to examine the effects of Interactive Technology Enhanced Coaching (ITEC) versus Interactive Technology (IT) alone in achieving BP control, adherence to antihypertensive medication, and adherence to lifestyle modifications among Black women diagnosed with and receiving medication for their hypertension. Participants completed a 6‐week Chronic Disease Self‐Management Program (CDSMP), and 83 participants were randomly assigned to ITEC versus IT. Participants were trained to use three wireless tools and five apps that were synchronized to smartphones to monitor BP, weight, physical activity (steps), diet (caloric and sodium intake), and medication adherence. Fitbit Plus, a cloud‐based collaborative care platform was used to collect, track, and store data. Using a mixed‐effects repeated measures model, the main effect of group means indicated no significant difference between the treatment and referent groups on study variables. The main effect of time indicated significant differences between repeated measures for systolic BP ( p  < .0001), weight ( p  < .0001), and steps ( p  = .018). An interaction effect revealed differences over time and was significant for study measures except diastolic BP. An important goal of this preliminary analysis is to help Black women prioritize self‐care management in their everyday environment. Future research is warranted in a geographically broader population of hypertensive Black women.